Rifamycin congeners kanglemycins are active against rifampicin-resistant bacteria via a distinct mechanism - James Peek (Nature Portfolio, 2018)
Resistance to rifamycin antibiotics, which target bacterial RNA polymerases, is a growing problem. Here, the authors identify gene clusters from soil metagenomes encoding production of rifamycin analogues that are active against rifampicin-resistant bacteria through a distinct mechanism.